Clinical aspects of magnesium physiology in patients on dialysis. Issue 5 (13th June 2017) - Misra, Paraish S.; Nessim, Sharon J.
Abstract: Magnesium balance is infrequently discussed in the dialysis population, and the clinical consequences of derangements in magnesium homeostasis are incompletely understood. There is an association between hypomagnesemia and adverse outcomes including increases in cardiovascular disease and mortality, while elevated magnesium levels have also been linked with complications such as osteomalacia. In this review, we discuss the features of magnesium physiology relevant to dialysis patients and provide an updated summary of the literature linking magnesium derangements with bone disease, cardiovascular disease, sudden cardiac death, and mortality.